1989
DOI: 10.1002/eji.1830190521
|View full text |Cite
|
Sign up to set email alerts
|

Collagen receptor on T lymphocytes and the control of lymphocyte motility

Abstract: Human lymphocytes, freshly isolated from blood, were allowed to settle on surfaces coated by collagen type 1, fibronectin, laminin, IgG or albumin at different concentrations. In separate cultures the lymphocytes were also exposed to these proteins in soluble form. The lymphocytes, predominantly T cells, attached to two-dimensional collagen substrata both in the presence and absence of serum but did not adhere or adhered poorly to substrata coated with fibronectin, laminin, IgG and albumin. In contrast, T blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…A previous report of a "130-kDa" collagen-binding lymphocyte membrane molecule may also have beenVLA-2 [9]. It has been known for some time that platelet VLA-2 specifically binds collagen [ll, 12].We show here that either on intact cells or in cell lysates,VLA-2 is the integrin used by Tcells as a collagen-binding receptor.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A previous report of a "130-kDa" collagen-binding lymphocyte membrane molecule may also have beenVLA-2 [9]. It has been known for some time that platelet VLA-2 specifically binds collagen [ll, 12].We show here that either on intact cells or in cell lysates,VLA-2 is the integrin used by Tcells as a collagen-binding receptor.…”
Section: Discussionmentioning
confidence: 69%
“…For example, collagen enhances phagocytic function of monocytes via activation of CR and FcyR [7] and over a longer time period, causes differentiation of monocytes [8]. Tcells in contact with collagen for a 24 h period develop motile behavior [9] and collagen has also been suggested to provide a costimulus for CD3-mediated T cell proliferation [lo].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytes have also been demonstrated to express a receptor for collagen [43][44][45], to adhere to collagen [43][44][45][46], and to disrupt and degrade collagen matrices [46][47][48][49][50]. Here, we have demonstrated that approximately half of the cells in a SUP-T1 population actively translocated across the surface of a dehydrated or hydrated collagen gel and that cells readily penetrated hydrated collagen gels.…”
Section: Behavior On Collagenmentioning
confidence: 72%
“…Lymphocytes have been demonstrated to invade collagen gels [41,42] and collagen has been demonstrated to enhance leukocyte motility [42,43]. Lymphocytes have also been demonstrated to express a receptor for collagen [43][44][45], to adhere to collagen [43][44][45][46], and to disrupt and degrade collagen matrices [46][47][48][49][50].…”
Section: Behavior On Collagenmentioning
confidence: 99%
“…Moreover, ECM components can modulate lymphocyte functions through specific interactions, possibly mediated by VLA integrins [40,41]. This accumulation of ECM proteins in AITD, caused by high density of specific VLA receptors, may not only serve to anchor T cells to different components of the ECM, but also be a strong stimulus to intrathyroidal lymphocytes, enhancing proliferation and motility of these cells [42].…”
Section: Discussionmentioning
confidence: 99%